A library-publisher partnership for open access: building an innovative relationship between scholarly publishers and academic libraries - Ward, Monica; Lavoie, Joanie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
This article presents an overview of a strategic partnership undertaken by the Canadian Research Knowledge Network (CRKN) and the Érudit Consortium (Érudit) to support the move towards open access for Canadian francophone scholarly journals. CRKN and Érudit have had a relationship through a traditional commercial subscription model since 2008. In 2014, the two organizations recognized the need for a new relationship that would address two major challenges: the fragility of the Canadian not-for-profit scholarly publishing environment and the increasing pressure from libraries and funding agencies for scholarly journals to move towards open access. Érudit and CRKN have worked collaboratively to create an innovative partnership, which provides a framework for a new relationship between publishers and libraries, and helps to provide financial support to Canadian publishers during the transition to a fully open access model. This paper presents the perspectives of the two organizations involved in the partnership by outlining the common goals, objectives, and strategy, as well as the differing needs and perspectives of libraries and publishers. It summarizes the key aspects of the partnership as well as the challenges faced. Through this case study, the authors demonstrate how university libraries can play an active role in working with journals to support open access to research.